Protocol to establish standards for the elements infection prevention and control programs and competencies for infection control professionals in Australian residential aged care homes - Ramon Z. Shaban; Kate Curtis; Margaret Fry; Brendan McCormack; Deborah Parker; Deborough Macbeth; Brett G. Mitchell; Phillip L. Russo; N. Deborah Friedman; Noleen Bennett; Lucy Thompson; Jo-Ann Dalton; et al. (PLoS ONE, 2025)
The COVID-19 pandemic elucidated the importance of infection prevention and control (IPC) in residential aged care homes (RACHs), both on the health and wellbeing of its residents, and the staff and clinicians who care for them. While considerable efforts have been made in Australia to improve IPC both during and in the aftermath of the COVID-19 pandemic, many of these resources remain reliant on evidence originating from hospitals and acute healthcare settings. This research aims to establish the core minimum components that will populate standards for IPC programs and governance (Stream A) and for professional practice and competencies (Stream B) in RACHs. This research will be completed using a sequential three-phase design. In Phase 1, two integrative literature reviews will be completed to synthesise the elements of current global IPC programs and professional competencies in RACHs. In Phase 2, a qualitative analysis of IPC programs and professional practice in Australian RACHs using a combination of surveys and interviews will be completed. Finally, in Phase 3, an e-Delphi will be conducted to collate expert opinion and generate consensus on the minimum components of the IPC program and professionals who administer them in RACHs. The final standards and resources will be collaboratively designed with aged care partners, industry leaders, professional bodies and key Australian health policymakers. These standards seek to empower IPC and aged care staff, not only by ensuring that they are well-equipped with the knowledge and skills to implement effective IPC programs themselves, but also that the organisation is adequately prepared to provide the resources and governance systems.